Intrabony Defects, Open‐Flap Debridement, and Decortication: A Randomized Clinical Trial. Issue 1 (1st January 2014) - Crea, Alessandro; Deli, Giorgio; Littarru, Cristiano; Lajolo, Carlo; Orgeas, Gianluca Vittorini; Tatakis, Dimitris N.
Abstract : Background: Intramarrow penetration (IMP) is often incorporated in regenerative periodontal surgical procedures. However, the actual benefits of adding IMP to such a procedure remain undocumented. The purpose of this randomized controlled trial was to investigate the contribution of IMP to the outcomes of open‐flap debridement (OFD) treatment of intrabony defects. Methods: Forty‐two chronic periodontitis patients, each contributing a 2‐wall, 3‐wall, or combined 2‐ to 3‐wall intrabony defect, were treated. Sites were randomly assigned into one of two groups: control (OFD alone) or test (OFD + IMP). Papilla preservation flaps were raised, and defects were thoroughly debrided. In the control group, complete primary closure of flaps was ensured after debridement. In the test group, IMP was performed before flap closure, using a round bur to penetrate the cortical defect wall. Clinical and radiographic parameters were assessed at baseline and 12 months after treatment. Results: At baseline, there were no statistically significant differences between groups. At 12 months, both groups experienced significant improvements, in terms of probing depth reduction, clinical attachment level (CAL) gain, and bone level (clinical and radiographic). The test group experienced significantly greater clinical bone gain (3.07 ± 1.74 mm) and prevalence of CAL gain ≥2 mm (93% of sites) compared with the control group (1.76 ± 2.71 mm, P <0.03; 62%, P = 0.024). The test treatment benefits were particularly evident in mandibular sites, in which OFD + IMP doubled the radiographic bone gain obtained by OFD alone. Conclusion: Addition of IMP to an OFD procedure used to treat intrabony defects results in statistically and clinically significant enhancement of both clinical and radiographic outcomes.